2021
DOI: 10.3390/coatings11121522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doping Element and Electrolyte’s pH on the Properties of Hydroxyapatite Coatings Obtained by Pulsed Galvanostatic Technique

Abstract: Hydroxyapatite (HAp) is the most widely used calcium phosphate as a coating on metal implants due to its biocompatibility and bioactivity. The aim of this research is to evaluate the effect of the pH’s electrolyte and doping element on the morphology, roughness, chemical, and phasic composition of hydroxyapatite-based coatings obtained by pulsed galvanostatic electrochemical deposition. As doping elements, both Sr and Ag were selected due to their good osseoinductive character and antibacterial effect, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 81 publications
(98 reference statements)
1
13
0
1
Order By: Relevance
“…Our previous results [56], which showed that the Sr content reached 3.5 at.%, suggested that the Sr ions replaced part of the Ca(I) site. Similarly, Ag + ions substituted Ca 2+ ions within the HAp lattice, preferring the Ca(I) site, which led to an increment in the lattice parameters due to the greater ionic radius (0.128 nm vs. 0.099 nm) [28].…”
Section: Coating Thicknessmentioning
confidence: 83%
See 3 more Smart Citations
“…Our previous results [56], which showed that the Sr content reached 3.5 at.%, suggested that the Sr ions replaced part of the Ca(I) site. Similarly, Ag + ions substituted Ca 2+ ions within the HAp lattice, preferring the Ca(I) site, which led to an increment in the lattice parameters due to the greater ionic radius (0.128 nm vs. 0.099 nm) [28].…”
Section: Coating Thicknessmentioning
confidence: 83%
“…The electrolyte concentrations along with the electrochemical parameters used are presented in Table 1, and a full description of the electrochemical deposition is available in Ref. [56]. The coating deposition was carried out with a potentiostat/galvanostat PARSTAT MC equipped with a PMC-1000 module (Princeton Applied Research-AMETEK, Berwyn, PA, USA) using the galvanostatic pulse technique.…”
Section: Electrochemical Deposition Of the Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…During deposition, the ionic substituents are integrated into the calcium phosphate lattice to enhance the biological properties of the coating. Several ions are described in the scientific literature with different biological effects [139][140][141][142][143][144][145][146][147].…”
Section: Ionic Substitution To Enhance the Properties Of Electrodepos...mentioning
confidence: 99%